The Effectiveness of Oxytocin Massage in Accelerating the Third Stage of Labor - Marwati, Marwati (Institute of Accounting Research and Novation (IARN), 2024)
This study investigates the effectiveness of oxytocin massage in accelerating the third stage of labor, aiming to enhance maternal outcomes and improve the overall childbirth experience. A randomized controlled trial was conducted involving pregnant women in labor, comparing a group receiving oxytocin massage with a control group receiving standard care. The primary outcomes measured were the duration of the third stage of labor and the incidence of postpartum hemorrhage. Results indicated that the oxytocin massage group experienced a significantly shorter duration of the third stage of labor and a reduced incidence of postpartum hemorrhage compared to the control group. Additionally, participants in the oxytocin massage group reported higher levels of maternal satisfaction. These findings suggest that oxytocin massage is an effective complementary therapy that can enhance labor management practices. The study highlights the importance of integrating holistic approaches in obstetric care, promoting better maternal and neonatal health outcomes. Future research should further explore the implications of oxytocin massage and similar interventions to optimize labor management and improve the childbirth experience for diverse populations.